MICS : micro-incision cataract surgery - Alió, Jorge; Rodríguez Prats, José Luis; Galal, Ahmed; Agarwal, Amar; Packard, Richard (Panamá : Highlights of Ophthalmology, 2004)
Trata el arte en las técnicas quirúrgicas del catarata de micro-incisión
CONTENTS REFRACTIVE SURGERY WITH PHAKIC INTRAOCULAR LENSES PART I: BASIC PRINCIPLES OF REFRACTIVE SURGERY WITH PHAKIC IOLs. PART II: IMPLANTATION OF PHAKIC INTRAOCULAR LENSES
Incluye subject index
Incluye bibliografía
Keywords: CIRUGÍA DE CATARATAS -- MICRO-INCISION